Imaging of Tropical Chronic Pancreatitis—A Unique Clinico-Radiological Entity - Kulkarni, Chinmay Bhimaji; Sekhar, Resmi; Moorthy, Srikanth; Pullara, Sreekumar Karumathil; Prabhu, Nirmal Kumar; Kannan, Ramiah Rajesh (Journal of Gastrointestinal and Abdominal Radiology, 2019)
Tropical chronic pancreatitis (TCP) is a unique juvenile nonalcoholic form of chronic pancreatitis prevalent in tropical developing countries. TCP is characterized by the younger age of onset, rapid progression, higher prevalence of diabetes and pancreatic calculi, and greater propensity to develop pancreatic malignancy. Identifying the distinct imaging features is critical for the diagnosis of TCP. Awareness of this condition will not only enable the radiologist to recognize it early but also help in better management. In this article, we review the etiopathogenesis, distinct imaging features, and complications of TCP.
Keywords: chronic calcific pancreatitis; tropical pancreatitis; mutation; computed tomography; magnetic resonance imaging; pancreatic malignancy